2022
DOI: 10.48550/arxiv.2203.12442
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Plasma Processing for In-Situ Field Emission Mitigation of Superconducting Radiofrequency (SRF) Cryomodules

M. Martinello,
P. Berrutti,
B. Giaccone
et al.

Abstract: Field emission (FE) is one of the main limiting factors of superconducting radiofrequency (SRF) cavities operating in accelerators and it occurs whenever contaminants, like dust, metal flakes or even absorbates, are present on the surface of the cavity high electric field region. Field emission reduces the maximum achievable accelerating field and generates free electrons that may interact with the beam, damage or activate the beamline. One practical method that can be used to mitigate this problem is in-situ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Promising R&D directions are being pursued for increasing gradient, including new superconducting materials, travelling wave cavities, new cell shapes for standing wave structures, cleanroom robotics to reduce field emission, layered superconductor structures, and new impurity doping treatments, as well as more fundamental explorations of the limits of RF superconductivity, such as the use of "slow surface" materials that could prevent dissipation from magnetic flux penetration. For examples of SRF R&D directions, see references [102][103][104][105][106][107][108]. There are many exciting ideas to pursue.…”
Section: Srf For Future Collidersmentioning
confidence: 99%
“…Promising R&D directions are being pursued for increasing gradient, including new superconducting materials, travelling wave cavities, new cell shapes for standing wave structures, cleanroom robotics to reduce field emission, layered superconductor structures, and new impurity doping treatments, as well as more fundamental explorations of the limits of RF superconductivity, such as the use of "slow surface" materials that could prevent dissipation from magnetic flux penetration. For examples of SRF R&D directions, see references [102][103][104][105][106][107][108]. There are many exciting ideas to pursue.…”
Section: Srf For Future Collidersmentioning
confidence: 99%
“…Hence, developing new cleaning methods [24], better cryomodule integration techniques, e.g., by employing robot-assisted assembly, and post-integration mitigation methods remain important R&D topics. White Paper [25] describes recent developments and future perspectives for one of the FE mitigation methods, in situ plasma processing. Plasma processing of SRF cavities was developed originally at Oak Ridge National Laboratory (ORNL), where it was demonstrated that a plasma of mixture of neon and a small percentage of oxygen reduces hydrocarbon-related field emission in the Spallation Neutron Source (SNS) cavities.…”
Section: Superconducting Rf Cavitiesmentioning
confidence: 99%